EKSPERIMENTASI PEMBELAJARAN MATEMATIKA MENGGUNAKAN PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION DAN TIPE GROUP INVESTIGATION PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN KUADRAT DITINJAU DARI GAYA BELAJAR KOLB PADA SISWA SMA NEGERI KELAS X - Harmini, Triana; Sujadi, Imam; Sari S, Dewi Retno (Jurnal Pembelajaran Matematika, 2014)
Abstract:The objectives of this research were to determine: (1) which students had the better mathematics learning achievement, instructed with TAI, GI, or direct instruction;  (2) which students had the better mathematics learning achievement, those with the converger, diverger, assimilator, or accommodator learning style; (3) in each learning style, which  students had better mathematics learning achievement, instructed with TAI, GI, or direct instruction; (4) in each learning model, which students had a better mathematics learning achievement, those with the converger, diverger, assimilator, or accommodator learning style. This study was  aquasi-experimental study with 3 x 4 factorial designs. Data analysis used unbalanced two-way ANAVA with a significance level of 5%. The study population was a tenth grade student of State SMA in Ponorogo in academic year of 2013/2014. Sampling was done by stratified cluster random sampling technique. The study sample consisted of students in 3 schools namely SMA Negeri 3 Ponorogo, SMA Negeri 1 Kauman, and SMA Negeri 1 Balong with a sample size of 275 students.. The results of the research are as follows. (1) The students instructed with TAI had learning achievement as good as GI, those with TAI had learning achievement better than those with direct instruction, while those GI had learning achievement as good as those with direct instruction. (2)The students with the converger learning style had learning achievement as good as those with the diverger learning style, the students with the converger learning style had learning achievement better than those with the assimilator and accommodator learning style, the students with the diverger, assimilator, and   accommodator learning style had a same learning achievement. (3) In each learning style, the students mathematics learning achievement was in consistency with the result (1); (4) In each learning model, the students mathematics learning achievement was in consistency with the result (2). Keywords: TAI, GI, Direct Instruction, learning styles, and learning achievement